Ретроспективний аналіз процесу євроатлантичної інтеграції України - Гороть, А.; Horot, A. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2014)
У даній статті проаналізовано історичні процеси євроінтеграції до Європейських і Євроатлантичних об’єднань. Разом з тим вважаємо за доцільне при аналізі проблеми інтеграційної політики України, її доцільності і характеру врахувати також негативні аспекти діяльності на міжнародній арені при визначенні зовнішньополітичного курсу не тільки України після здобуття незалежності, але й певних суб’єктів Організації Північноатлантичного договору. У статті запропоновано ретроспективний аналіз низки факторів та умов, за наявності яких стає зрозуміло чому досить тривалий час процес євроатлантичної інтеграції не був здійснений. This article deals with the historical process of European integration to European and Euro-Atlantic organizations. However, we consider it appropriate when analyzing the problem of integration policy of Ukraine, its expediency and nature take into account the negative aspects on the international arena in determining foreign policy not only for Ukraine, but for the specific subjects of NATO. This paper proposes a retrospective analysis of factors and conditions under which it becomes clear why Euro-Atlantic integration hasn’t been carried into practice for a long time. Inconsistent Ukraine in its relations with the West at the beginning of independence has led to certain problems in external relations today. At first Ukraine declared itself a neutral state, and in May 2002, when strategy of Ukraine on North Atlantic Treaty Organization was approved, our government announced its intention to join NATO. The strongest argument was considered a statement of the fact that when the question of the historical necessity of union with one or a group of countries appeared, it was logical to provide this process with a stable, strong partner
Retrospective Analysis of the Euro-Atlantic Integration Process of Ukraine.
Keywords: двосторонні відносини; Євроатлантична інтеграція; НАТО; Республіка Польща; партнерство; Україна; bilateral relations; Euro-Atlantic integration; NATO; Poland; partnership; Ukraine